2002
DOI: 10.1002/etc.5620210925
|View full text |Cite
|
Sign up to set email alerts
|

Development of photosynthetic biofilms affected by dissolved and sorbed copper in a eutrophic river

Abstract: Photosynthetic biofilms are capable of immobilizing important concentrations of metals, therefore reducing bioavailability to organisms. But also metal pollution is believed to produce changes in the microalgal species composition of biofilms. We investigated the changes undergone by natural photosynthetic biofilms from the River Meuse, The Netherlands, under chronic copper (Cu) exposure. The suspended particles in the river water had only a minor effect on reduction of sorption and toxicity of Cu to algae. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
1
33
1
Order By: Relevance
“…For example, topminnows (killifishes) that showed the highest Cu concentrations are known to feed opportunistically on biofilm at the water surface, whereas gobies that are the least contaminated species feed on benthic prey and bottom detritus. Because biofilms are huge reservoirs of organic biomass that can greatly accumulate contaminants (Barranguet et al 2002), feeding on water surface might explain why killifishes had the highest Cu concentration among fish. However, metal concentrations in sunfish varied greatly among species (Table 2), despite the fact that sunfish species shared similar feeding characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, topminnows (killifishes) that showed the highest Cu concentrations are known to feed opportunistically on biofilm at the water surface, whereas gobies that are the least contaminated species feed on benthic prey and bottom detritus. Because biofilms are huge reservoirs of organic biomass that can greatly accumulate contaminants (Barranguet et al 2002), feeding on water surface might explain why killifishes had the highest Cu concentration among fish. However, metal concentrations in sunfish varied greatly among species (Table 2), despite the fact that sunfish species shared similar feeding characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Genter et al (1987) noted a shift in phototrophic community composition from diatoms to cyanobacteria and green algae after exposure to Zn. Other studies also reported biofilm community shifts towards a dominance of cyanobacteria after long-term exposure to metals, indicating that cyanobacteria may be more tolerant to metal contamination (Barranguet et al 2002(Barranguet et al , 2003Serra et al 2009). Cyanobacteria are known to lack a xanthophyll cycle, but still contain significant amounts of zeaxanthin and other xanthophylls (Jeffrey and Vesk 1997), which could help explain their high tolerance to metals.…”
Section: Effects Of Zn Contamination On the Induced Tolerance Of The mentioning
confidence: 93%
“…These epilithic, epiphytic, or epipelon assemblages are generally described as biofilms (30). Barranguet et al, studying heavy metal effects on aquatic biofilms, showed that Cu affects the physiology of phototrophic organisms (1), that it accumulates in phototrophic biofilms proportionally to the concentration of exposure, and that some algal species react morphologically to an increased Cu concentration (3). However, the measured Cu effects on the photosystem were not related to changes occurring in the composition of the phototrophic community as observed by microscopy.…”
mentioning
confidence: 99%
“…These authors did not detect large differences between bacterial communities growing at Cu concentrations ranging from 3 to 87 M. Our results suggest that the complex and organized structure of the biofilm (10,18,30) would not protect the bacterial community in the same way that sediments do, even through the formation of extracellular polymeric substances was found to increase several resistance capacities of each encased organism (24) by reducing the bioavailability of heavy metals (33). Short-and long-term toxicity tests of heavy metals on aquatic biofilms have focused either on the response of the phototrophic compartment (1,2,5,17) or on that of the heterotrophic compartment (34), but toxic effect assessments based on physiological tests (3,19) or studies considering the biofilm as a whole have not investigated the effect of Cu (6,23). Possible interactions between phototrophic and heterotrophic compartments of a biofilm may be disturbed when one compartment is severely affected by a stress factor, e.g., an increase in toxicant concentration.…”
mentioning
confidence: 99%